Cultivation and Differential Development of Mental Health and Subjective Happiness of Seniors Based on Sports Dance - Baoling Ma; Baojuan Ma; Xiangdong Wang; Xiaohong Zhao; Gang Huang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Age-friendly sports can effectively alleviate the pressure of population aging on economy and society. Many studies have discussed the motives, current states, and favorite sports of seniors participating in physical exercise. However, there is little report on the evaluation of the health of seniors in sports dance, or the gradual cultivation of mental health and subjective happiness of seniors. Therefore, this paper explores the cultivation and differential development of mental health and subjective happiness of seniors based on sports dance. Firstly, a scientific evaluation index system (EIS) was constructed for the health of seniors in sports dance. Next, a matter-element extension model was established, and the detection methods were developed for the evaluation criteria. Finally, the flow of index weighting was explained. Through experiments, the authors analyzed the difference among seniors in mental health improvement and subjective happiness cultivation under the intervention of sports dance. The research results provide a reference for how the mental health and subjective happiness of seniors are affected by the scientific training and benign development of sports dance, as well as long-term exercise of sports dance.